2020
DOI: 10.1159/000509957
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MAFG-AS1 Promotes the Progression of Bladder Cancer by Targeting the miR-143-3p/COX-2 Axis

Abstract: <b><i>Background:</i></b> Long noncoding RNAs (lncRNAs) are potential biomarkers that are very important for the development of cancer. Studies show that lncRNAs are significantly correlated with the carcinogenesis and progression of bladder cancer (BLCA). In this research, we aimed at probing into the role of lncRNA MAFG-AS1 in the tumorigenesis of BLCA. <b><i>Methods:</i></b> RT-qPCR was employed to detect MAFG-AS1 expression in BLCA tissues and cells. MAFG-AS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Firstly, MAFG-DT as a part of lncRNAs signature of tumor-infiltrating B lymphocytes had some predictive value for the survival outcomes and immunotherapy response of patients with antiprogrammed death-1 (PD-1) therapy and added significant predictive power to current immune checkpoint gene markers [ 32 ]. Next, Li et al reported that silencing of MAFG-AS1 inhibited BC cell proliferation, metastasis, and invasion, while overexpression of MAFG-AS1 in BC cell had opposite biological effects, and it was further confirmed that MAFG-AS1/miR-143-3p/COX-2 axis was involved in the progression of BC [ 33 ]. Besides, Xiao et al showed that MAFG-AS1 can promote BC proliferation, invasion, metastasis, and EMT in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…Firstly, MAFG-DT as a part of lncRNAs signature of tumor-infiltrating B lymphocytes had some predictive value for the survival outcomes and immunotherapy response of patients with antiprogrammed death-1 (PD-1) therapy and added significant predictive power to current immune checkpoint gene markers [ 32 ]. Next, Li et al reported that silencing of MAFG-AS1 inhibited BC cell proliferation, metastasis, and invasion, while overexpression of MAFG-AS1 in BC cell had opposite biological effects, and it was further confirmed that MAFG-AS1/miR-143-3p/COX-2 axis was involved in the progression of BC [ 33 ]. Besides, Xiao et al showed that MAFG-AS1 can promote BC proliferation, invasion, metastasis, and EMT in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…HOTAIR promotes the proliferation, migration, and invasion of BCa cells by regulating CCNJ and inhibiting miRNA-205 [ 116 ]. MAFG-AS1 regulates the miR-125b-5p/SphK1 and the miR-143-3p/COX-2 axes to promote the proliferation, migration, and invasion of BCa cells [ 117 , 118 ]. SPRY4-IT1 sponges miR-101-3p to promote the proliferation, migration, and invasion of BCa cells by upregulating EZH2 [ 119 ].…”
Section: Invasion Migration and Metastasismentioning
confidence: 99%
“…Increased ARSR expression is positively correlated with higher histological grade and larger tumor size [ 146 ]. SNHG3 [ 137 ], RMRP [ 132 ], PCAT6 [ 189 ], and LSINCT5 [ 149 ] expression positively correlated with tumor size and TNM stage, while high expression of MAFG-AS1 [ 118 , 153 ], SNHG7 [ 90 , 103 ], and TMPO-AS1 [ 33 , 34 ] was closely related to histological grade, tumor size, TNM stage, and clinical stage of BCa patients. However, many lncRNAs are important for tumor size suppression.…”
Section: Lncrnas Are Associated With Clinicopathological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 miR-143-3p was found to demonstrate ectopic expression and was directly related to the progression and prognosis of a variety of cancers. 21,22 Moreover, miR-143-3p was found to be involved in the osteogenic differentiation of BMSCs. 23 However, the role of miR-143-3p in the process of osteogenic differentiation of ADSCs remains unknown.…”
Section: Introductionmentioning
confidence: 99%